How to use Wilsondisc ([New York] H.W. Wilson, 1992)
A CD-ROM information retrieval system. Introduces Wilsondisc features like the Browse mode, Wilsearch mode, Wilsonline mode, and guide in customizing Wilsondisc.
Keywords: CD-ROM.; Periodicals -- Indexes; Wilsondisc; Library science